Factors Influencing the Utilization of Onion Peel Waste as Natural Pesticides in Sungai Pauh Village, Langsa Barat Subdistrict, Langsa City, 2025 - Megawati Megawati; Aura Anzila; Intan Kumala Dewi (Journal of Innovative and Creativity, 2026)
Household organic waste, particularly shallot and garlic peel waste, has the potential to be utilized as natural pesticides that are environmentally friendly and safe for human health. However, the utilization of this waste at the household level remains limited. This study aimed to analyze the knowledge, attitudes, and practices of housewives regarding the utilization of shallot and garlic peel waste as natural pesticides in Sungai Pauh Village, Langsa Barat Subdistrict, Langsa City. This study employed a quantitative analytical design with a cross-sectional approach. Data were collected using a structured questionnaire measuring respondents’ knowledge, attitudes, and practices related to the utilization of shallot and garlic peel waste. The data were analyzed using univariate analysis to describe the distribution of each variable. The results showed that most respondents had a moderate level of knowledge regarding the utilization of shallot and garlic peel waste as natural pesticides. The majority of respondents demonstrated positive attitudes toward the use of natural pesticides, perceiving them as safer and more environmentally friendly than chemical pesticides. However, actual implementation remained low, as most respondents had not practiced utilizing shallot and garlic peel waste as natural pesticides in their household gardening activities. In conclusion, although housewives generally possess adequate knowledge and positive attitudes toward the utilization of shallot and garlic peel waste, these factors have not been fully translated into practical actions. This study highlights the need for educational interventions accompanied by practical training and community support to promote sustainable household waste management and environmentally friendly pest control practices.